2021
DOI: 10.1111/codi.15786
|View full text |Cite
|
Sign up to set email alerts
|

Finding the needle in the haystack: the diagnostic accuracy of the faecal immunochemical test for colorectal cancer in younger symptomatic patients

Abstract: Aim Detection of early onset colorectal cancer is challenging, and remains a rare diagnosis amongst younger people with gastrointestinal symptoms. We investigated whether faecal immunochemical testing (FIT) could identify younger patients at higher risk of colorectal cancer or serious bowel disease including colorectal cancer, inflammatory bowel disease or advanced adenomas. Methods A subgroup analysis was performed of symptomatic patients under 50 years of age (<50) from the NICE FIT study, a multicentre, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…A diagnostic test that can identify those younger patients at risk of cancer may therefore be useful as an adjunct to decide on referral to secondary care for further investigation. The diagnostic accuracy data of FIT in younger patients (<50) was the primary endpoint in one study, 116 but reported in subgroup analyses in three further studies. 13 29 53 Souza et al investigated the diagnostic accuracy of FIT in 9822 symptomatic patients in the UK, and had a particular focus on 1103 symptomatic patients under the age of 50.…”
Section: Fit In Specific Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A diagnostic test that can identify those younger patients at risk of cancer may therefore be useful as an adjunct to decide on referral to secondary care for further investigation. The diagnostic accuracy data of FIT in younger patients (<50) was the primary endpoint in one study, 116 but reported in subgroup analyses in three further studies. 13 29 53 Souza et al investigated the diagnostic accuracy of FIT in 9822 symptomatic patients in the UK, and had a particular focus on 1103 symptomatic patients under the age of 50.…”
Section: Fit In Specific Populationsmentioning
confidence: 99%
“…The diagnostic accuracy data of FIT in younger patients (<50) was the primary endpoint in one study,116 but reported in subgroup analyses in three further studies 13 29 53. Souza et al investigated the diagnostic accuracy of FIT in 9822 symptomatic patients in the UK, and had a particular focus on 1103 symptomatic patients under the age of 50 116. The prevalence of CRC was 1.5% (16/1103) in younger symptomatic patients.…”
Section: Fit In Specific Populationsmentioning
confidence: 99%
“…Despite this, 0.36% is much lower than the 4%-6% of cancers which may be missed when colonoscopy is used as a screening tool [15][16][17]. A recent subgroup analysis of a multicentre trial looking into the use of FIT as a predictive tool for CRC has shown that a positive f-Hb using FIT on symptomatic patients under the age of 50 may indicate the need for referral for investigation of CRC or serious bowel TA B L E 6 Subgroup analysis of the endoscopic findings within the FIT triage cohort based on FIT cut-off levels compared to the total number of patients within the FIT triage cohort [18]. The age group is significantly younger than the median age of the cohort in our study (72 years).…”
Section: Discussionmentioning
confidence: 99%
“…Data had been limited regarding the diagnostic accuracy of qFIT in symptomatic younger patients with suspected CRC symptoms. A subgroup analysis of the 2021 NICE FIT study focused on younger patients (aged <50) found a moderate sensitivity of 87.5% and 81.3% at lower cutoffs of 2 and 10 μg/g, but the prevalence was 11.5% at the highest cutoff of 150 μg/g [23]. The negative predictive value for CRC remained above 99.5% at all cutoffs, and FIT was associated with a high prevalence of significant bowel disease (46.1%) at the 10 μg/g cutoff recommended by NICE DG30 [24].…”
Section: Symptomatic Patientsmentioning
confidence: 99%
“…The recent collection of studies on quantitative faecal immunochemical test (qFIT) use in symptomatic patients in Colorectal Disease [7][8][9][10] and its widespread adoption as a screening modality in Europe has compelled reflection on its use in practices for both asymptomatic and symptomatic CRC detection and screening in the US. Other healthcare structures are similarly structured.…”
mentioning
confidence: 99%